FE/MG-FE/MN RELATIONS OF METEORITES AND PRIMARY HETEROGENEITY OF PRIMITIVE ACHONDRITE PARENT BODIES - CHONDRITIC METEORITE CLASSIFIED BETWEEN E AND H CHONDRITE GROUPS - Goodrich C.A.; Delaney J.S. (My University, 2000)
We examine Fe-Mg-Mn relations of meteorites, as represented on plots of molar Fe/Mg ratio vs. molar Fe/Mn ratio, and use them to consider whether it is meaningful to classify achondrites as ''primitive'' or ''evolved.'' First, we demonstrate that Fe/Mg-Fe/Mn plots can be used to identify some of the major processes that have affected meteorite parent bodies, during both the nebular (condensation and accretion) and the planetary (igneous) stages of their evolution. Examination of compositions of chondrites on this diagram reveals distinct patterns that result from three nebular processes: (1) volatility-controlled Mn-Mg fractionation; (2) metal/silicate fractionation under highly reducing conditions; and (3) subsequent oxidation leading to variations in FeO/MgO ratio. Ordinary chondrites (OCs) show a characteristic pattern that records all three of these processes and suggests that the latter two are coupled.Examination of the compositions of achondrites on this diagram shows that all of those that have been classified as primitive (lodranites/acapulcoites, winonaites/IAB silicate inclusions, brachinites, and ureilites) are easily distinguished from those that have been classified as evolved (SNCs, HEDs, and lunar basalts). The Mn/Mg ratios of the former are chondritic, while those of the latter are superchondritic; hence, they plot in two graphically distinct regions of the Fe/Mg-Fe/Mn diagram. A simple melting calculation reveals that this distinction results principally because the former are residues and the latter are melts or cumulate products of melts, rather than because the latter are more evolved.Additionally, however, some of the groups classified as primitive achondrites show Fe/Mg-Fe/Mn patterns similar to that of OCs-constant (but distinct) MnO/MgO ratios over large ranges of FeO/MgO ratio. We argue that these trends reflect primary heterogeneity, resulting from the same nebular processes as those that affected OCs, and therefore preserve evidence that more of the materials that accreted to form planetesimals experienced these processes than is apparent from known chondrites. This evidence is preserved principally because these meteorites are residues. In contrast, groups commonly classified as evolved achondrites show Fe/Mg-Fe/Mn patterns that reflect only igneous processing, and any evidence for primary heterogeneity of their parent bodies has been obliterated. Again, this is principally because these meteorites represent melts, rather than beause they are more evolved. Usage of the terms primitive and evolved to describe achondrites should be clearly defined.